An Integrated DEMATEL-ANP Approach for Mobile Banking Adoptions in China Market. (10th October 2020) - Zhu, Xiaoning; Yan, Rui; Xu, Tian xing
Abstract : With the rapid development of the mobile device and Internet usage, the mobile banking has seen remarkable growth across the world, especially in the past few years, as one of the emerging financial innovations. This paper attempts to explore the mobile banking services offered by selected commercial Chinese banks. The main data of this study were obtained through the comprehensive evaluation of mobile banking services. The DEMATEL-ANP method was used to evaluate the main factors influencing the adoption of mobile banking. The results show that there is still big space for the improvement of the mobile banking services for the selected Chinese banks. The management significance and suggestions for these banks are also discussed.